Prevalence of Depression Among Women Using Hormonal Contraceptives in Mogadishu, Somalia: A Cross-Sectional Study - Yusuf AM; Warsame MO; Gedi S; Abdullahi NA; Ahmed DI (Dove Medical Press, 2024)
Abdirizak Mohamud Yusuf,1 Mohamed Omar Warsame,2 Saido Gedi,3 Naima Abdulkarim Abdullahi,4 Daud Ibrahim Ahmed5 1Department of Family Health, Federal Ministry of Health, Mogadishu, Somalia; 2School of Public Health and Research, Somali National University, Mogadishu, Somalia; 3Public Health Department, Erciyes University, Kayseri, Turkey; 4World Health Organization Emergency Program, WHO, Mogadishu, Somalia; 5Department of Training and Development, National Institute of Health, Mogadishu, SomaliaCorrespondence: Abdirizak Mohamud Yusuf, Email abdirizak.moh20@gmail.comBackground: Depression is a global health concern with significant consequences, especially for women. Hormonal changes and gender disparities contribute to its prevalence. Hormonal contraceptives are widely used among women of reproductive age, but some users report mood-related side effects.Purpose: This study aims to investigate the relationship between hormonal contraceptive use and depression among women in Mogadishu, Somalia.Methods: An analytical cross-sectional study was conducted at two hospitals in Mogadishu, targeting married women aged 15- 49 using hormonal contraceptives. A sample size of 227 participants was determined, and data was collected using semi-structured questionnaires, including the Patient Health Questionnaire-9 (PHQ-9) to assess depression. The data were analyzed using SPSS version 25, including multivariate logistic regression.Results: The prevalence of depression among participants was 33.5%, with significant associations observed between depression and occupation, income level, type of hormonal contraceptive used, and duration of contraceptive use. Housewives, individuals with lower income, users of oral pills and implant methods, as well as those with shorter durations of contraceptive use, constituted the high-risk groups for depression.Conclusion: Depression poses a concern among women using hormonal contraceptives in Mogadishu, Somalia. Healthcare providers should educate women about potential side effects and consider individualized contraceptive recommendations. Mental health support initiatives and awareness campaigns should be introduced. Future research is recommended to further understand and address depression in this context.Keywords: hormonal contraceptives, HC, reproductive health, depression, Somali women, cross-sectional study